2021
DOI: 10.3389/fonc.2021.668162
|View full text |Cite
|
Sign up to set email alerts
|

Acalabrutinib: A Selective Bruton Tyrosine Kinase Inhibitor for the Treatment of B-Cell Malignancies

Abstract: Bruton tyrosine kinase (BTK) is a validated target for treatment of B-cell malignancies, and oral inhibitors of BTK have emerged as a standard of care for these diseases. Acalabrutinib is a second generation, highly selective, potent, covalent BTK inhibitor that exhibits minimal off-target activity in in vitro assays, providing the potential to improve tolerability over the first-in-class BTK inhibitor, ibrutinib. Acalabrutinib was approved for the treatment of relapsed/refractory mantle cell lymphoma (MCL) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 68 publications
0
23
0
1
Order By: Relevance
“…Diarrhea is commonly observed AE in patients treated with BTKi. It is observed mainly in the first six months from beginning therapy, with a frequently observed self-limited course [148,149]. Similar incidence is observed between patients treated with ibrutinib and acalabrutinib [148,149].…”
Section: Diarrheamentioning
confidence: 55%
See 2 more Smart Citations
“…Diarrhea is commonly observed AE in patients treated with BTKi. It is observed mainly in the first six months from beginning therapy, with a frequently observed self-limited course [148,149]. Similar incidence is observed between patients treated with ibrutinib and acalabrutinib [148,149].…”
Section: Diarrheamentioning
confidence: 55%
“…It is observed mainly in the first six months from beginning therapy, with a frequently observed self-limited course [148,149]. Similar incidence is observed between patients treated with ibrutinib and acalabrutinib [148,149]. Temporary drug holds should be considered in the case of grade ≥3 diarrhea.…”
Section: Diarrheamentioning
confidence: 77%
See 1 more Smart Citation
“…Three phase 3 randomised controlled trials of acalabrutinib or zanubritinib, compared to ibrutinib in various lymphoma subtypes, have each demonstrated an improved safety profile of the second generation agents, and, particularly, lower rates of atrial fibrillation, which was observed in 2–2.5% with zanubrutinib and 9% acalabrutinib, compared to approximately 15% with ibrutinib [ 28 , 33 , 34 ]. Acalabrutinib has predominantly been developed in CLL and MCL, and is FDA approved for both indications [ 35 ]. A phase 2 study in treatment naïve and relapsed refractory WM showed high levels of efficacy in both settings, including ORR of 93% and PFS of 82% in relapsed disease at a median follow up of 27.4 months [ 27 ].…”
Section: Review Of Approved Small Molecule Inhibitorsmentioning
confidence: 99%
“…A pooled analysis of 610 patients on acalabrutinib revealed atrial fibrillation episodes of any grade at a rate of 2.3%. 47 In patients with relapsed/refractory CLL receiving therapy with acalabrutinib in the ASCEND trial, there was a 6% frequency of atrial fibrillation (9 of 154), reported at a median follow-up of 22 months. 29 In patients receiving frontline therapy with acalabrutinib in the ELEVATE-TN trial, the incidence of atrial fibrillation was 4% (7 of 179) in patients receiving treatment with acalabrutinib as monotherapy, 3% (6 of 178) in patients receiving acalabrutinib-obinutuzumab and 1% (1 of 169) in patients receiving obinutuzumab-chlorambucil, at a median follow-up of 28.3 months.…”
Section: Safety and Tolerability Of Acalabrutinib In Cllmentioning
confidence: 99%